CONTEMPORARY EDUCATION MANAGEMENT AS A SOCIAL AND CULTURAL PRACTICE - Gunadi, Lie Epifani Rachmad; Kumala, Milka (Four Son Scholarship, 2025)
This study presents a conceptual synthesis of contemporary education management through a Systematic Literature Review (SLR) approach, focusing on social and cultural dimensions. A literature review of publications from 2020 to 2024 emphasizes that education management practices cannot be separated from organizational culture, cultural values, and social interactions among educational actors. Organizational culture is a determining factor in management effectiveness, while cultural values and local wisdom shape institutional identity and guide decision-making. Managerial practices are also understood as a social arena, where negotiation, communication, and collaboration determine the successful implementation of education policies. This synthesis identifies research gaps related to cross-disciplinary integration between management theory, cultural anthropology, and social practices in education. Theoretical implications point to the importance of an integrative conceptual framework, while practical implications emphasize the development of adaptive, humanistic, and contextual educational management policies and practices. The results of this study are expected to serve as a reference for academics, practitioners, and policymakers in designing educational management that is relevant to contemporary socio-cultural dynamics.